Light isotope separation through the compound membrane of graphdiyne - Poteryaeva, Valentina A. (Membranes)
The separation of isotopes of one substance is possible within the framework of the quantum mechanical model. The tunneling effect allows atoms and molecules to overcome the potential barrier with a nonzero probability. The membranes of two monoatomic layers enhance the differences in the components' passage through the membrane, thereby providing a high separation degree of mixtures. The probability of overcoming the potential barrier by particles is found from the solving of the Schrodinger integral equation. Hermite polynomials are used to expand all the terms of the Schrodinger integral equation in a series to get a wave function. A two-layer graphdiyne membrane is used to separate the mixture.